Examining trust in the police and justice system among ethnic minority members: the case of Moroccan- and Turkish-Dutch citizens in the Netherlands - Meeusen, Cecil (European journal of criminology, 2024)
While extant studies indicate that ethnic minority citizens report relatively low levels of trust in the police and justice system, it is less clear how that trust can be explained. Thanks to its purposive oversampling of Dutch citizens with Turkish and Moroccan origins and nested structure (individuals clustered within neighbourhoods), the Netherlands Longitudinal Lifecourse Study has enabled us to scrutinise which of the following factors contribute to their trust in the police and justice system: (a) being in a weak socioeconomic position; (b) individual social capital; (c) (perceiving to be) living in underprivileged neighbourhoods characterised by disorder and low social capital; and (d) perceived discrimination. Multilevel structural equation modelling, allowing us to untangle individual perceptions from intersubjective neighbourhood-level conditions, reveals that Moroccan-Dutch citizens report less trust than Turkish-Dutch citizens. We find that perceived neighbourhood disorder and perceived discrimination link to lower trust, while traditional explanations such as socioeconomic position and social capital are far less relevant. We discuss our findings? implications for ongoing debates on, amongst others, the role of ethnicity and neighbourhood conditions in trust in the police and justice system.